Cannabinoids as Nutritional Supplements: Exploring The Potential Health Benefits and Regulatory Landscape - Minhaj Akhtar Usmani; Kainat Akhtar Usmani (Emerging Trends in Metabolites, 2024)
Cannabinoids, the bioactive compounds derived from the Cannabis sativa plant, have garnered increasing interest for their potential role as nutritional supplements. This abstract provides a succinct overview of cannabinoids as nutritional supplements. This review delves into the multifaceted aspects of cannabinoids, particularly their interaction with the endocannabinoid system (ECS) and their potential health benefits. The exploration begins by elucidating the intricate relationship between cannabinoids and the ECS, a vital regulatory system in the human body responsible for maintaining homeostasis. The review examines the potential health benefits associated with cannabinoids as nutritional supplements, including anti-inflammatory properties, stress and anxiety reduction, appetite regulation, and potential neuroprotective effects. Safety considerations take center stage, addressing the importance of quality and purity in cannabinoid-based products. The paper emphasizes the necessity for rigorous testing and standardized dosing recommendations, considering individual variability and potential adverse effects. Furthermore, it underscores the evolving regulatory landscape, discussing the global legal status of cannabinoids and the challenges posed by varying regulations. Further research on them as dietary supplements is needed to better understand the medical potential and safety of cannabis. Ongoing studies should focus on elucidating specific mechanisms of action within the ECS and exploring additional health benefits beyond those currently identified. As regulatory frameworks adapt globally, ensuring standardized production methods and clear labeling will be pivotal in promoting consumer trust and safety. Continued collaboration between researchers, regulators, and industry stakeholders is crucial for harnessing the benefits of cannabinoids while mitigating potential risks. Ultimately, this evolving field holds promise for novel therapeutic interventions, provided that scientific rigor and responsible oversight remain paramount. In conclusion, the paper highlights the dynamic nature of cannabinoids as a burgeoning field of research with promising implications for human health. As regulatory frameworks evolve, there is a need to strike a balance between guaranteeing consumer protection and providing access. The exploration of cannabinoids as nutritional supplements represents a multidimensional journey that necessitates continued research, responsible regulation, and informed consumer choices for the realization of their full potential.
Keywords: Cannabinoids; Cannabis sativa; anti-inflammatory properties; nutritional supplements